13 th International Workshop on Greenhouse Gas Measurements from Space : Book of Abstracts - Verronen, Pekka (Finnish Meteorological Institute, 2017)
The 13th International Workshop on Greenhouse Gas Measurements from Space (IWGGMS) will be held on 6-8 June, 2017, at the University of Helsinki in Helsinki, Finland. The workshop is organised by the Finnish Meteorological Institute with support from the University of Helsinki. The workshop gathers together more than 160 scientists from the EU, USA, Japan, China, Australia, Canada, and Russia. This report is the official abstract book of the workshop. Background. Success in space-based global measurement of greenhouse gases, such as carbon dioxide and methane, is critical for advancing the understanding of carbon cycle. The recent developments in observations and in interpreting the data are very promising. Space-based greenhouse gas measurement, however, poses a wide array of challenges, many of which are complex and thus demand close international cooperation. The goal of the workshop is to review the state of the art in remote sensing of CO 2 , CH 4 , and other greenhouse gases from space including the current satellite missions, missions to be launched in the near future, emission hot spots on regional and global scales, process studies and interactions of carbon cycle and climate, pre-flight and on-orbit instrument calibration techniques, retrieval algorithms and uncertainty quantification, validation methods and instrumentation, related ground-based, shipboard, and airborne measurements, and flux inversion from space based measurements. The workshop is part of the programme for the centenary of Finland's independence in 2017. The workshop is also one of the activities arranged by the Finnish Meteorological Institute to support Finland's chairmanship of the Arctic Council, 2017 - 2019. The workshop is sponsored by the Finnish Meteorological Institute, the University of Helsinki, the European Space Agency, the City of Helsinki, the Federation of Finnish Learned Societies, and ABB Inc.